Shading nets effect on the production and quality of blueberry fruit (Vaccinium corymbosum L.) cv. Brigitta - Rodríguez Beraud, Mario (2015)
Growth, development and fruit quality blueberry (Vaccinium corymbosum L.) variety Brigitta under different shade nets were evaluated. Assays were performed in plants 7 years in a commercial orchard Collipulli, Araucanía Region, Chile. Treatments were a control without shading and four types of screens: a red 40% and 18% shade; aluminized mesh with 40% shade and a black mesh 35% shade. In fruits shade of red mesh 40% greater equatorial and polar diameter were observed and three weeks later harvested the fruits of treatment without mesh. In growing shade 40% aluminized mesh phenological stages extension lag and the maximum weekly production two weeks over control was observed. The highest yields were observed in plants of treatment and control shade of red mesh 40%, with 11008 kg ha-1 and 10461 kg ha-1, respectively, while the lowest was in red mesh 18% with 9668 kg ha-1. The fruits grown under shade of red mesh 18% showed the highest number of fruits per plant with 1806 berries per plant, fruit weight less than 1.69 g with the strongest with 3.76 N mm-1 module deformability. Therefore, the largest weight berry fruits observed in non-mesh screen and 40% red shading, together with the increased size and performance.